Validation and utility of plasma neurofilament light as a biomarker for vascular cognitive impairment. (20th December 2022) - Kautz, Tiffany F; Mathews, Julia J; Parent, Danielle; Sudduth, Tiffany L; Liu, Qianqian; Wiedner, Crystal; Wang, Chen‐Pin; Mbangdadji, Djass; Bis, Joshua C; Sagare, Abhay P; Beiser, Alexa S; Pottanat, George; et al.
Abstract: Background: Neurofilament light chain (NfL) is a broad marker of neuroaxonal injury that is elevated in the CSF in those with vascular cognitive impairment and dementia (VCID). Blood and CSF levels highly correlate, making it an attractive peripheral marker for VCID pathology. As part of the MarkVCID consortium, we sought to evaluate the instrumental validity of plasma NfL using the Quanterix Simoa platform and assess its validity for risk stratification in clinical trials of VCID. Method: Plasma NfL was measured using HD‐X and HD‐1 Simoa instruments. For instrumental validation, we used samples from the MarkVCID consortium to evaluate intra‐ and inter‐plate reliability, test‐retest repeatability, and inter‐site reproducibility. We used linear regression models to assess the association of NfL with general cognitive function (GCF) as the primary outcome. In secondary analyses we assessed associations with white matter hyperintensities (WMH), an established small vessel disease marker. Models were adjusted for potential confounders. The clinical validation included established cohorts from the CHARGE consortium (i.e., CARDIA, ARIC, FHS, AGES; n=4, 772), the UKY ADRC (n=350), and the UCD ADRC (n=196). Additional analyses are underway in MarkVCID sites. Result: We found low coefficients of variation (average CV<12%), high inter‐site reproducibility (overall ICC = 0.93) and high repeatability in blood samples drawn within 30 days (ICC=0.968). There was high consistency across Quanterix instruments (HD‐X and HD‐1; R 2 ≥0.98) and kits (N4PA and single molecule NfL; ICC≥0.81). We observed consistent significant associations between higher NfL concentrations and worse GCF in CHARGE cohorts (meta‐analysis β=‐0.11; [95% CI ‐0.06; ‐0.17]), the UKY ADRC (β=‐0.16; [95% CI ‐0.27; ‐0.05]) and the UCD ADRC (UCD: β=‐0.28; [95% CI ‐0.48; ‐0.08). Secondary analyses revealed significant associations between elevated NfL concentrations and higher WMH burden in CHARGE cohorts and the UCD ADRC (P<0.01). Conclusion: Our results suggest plasma NfL can be reliably measured using the Quanterix platform, making this marker ideal for multi‐site clinical trials. We observed consistent associations for plasma NfL concentrations with cognition and WMH across independent samples, providing evidence that plasma NfL can be a useful biomarker for stratification in VCID trials.